BIOGEOCHEMICAL DATA FROM WELL PRESERVED 200 KA COLLAGEN AND SKELETAL REMAINS - Jones A.M.; O'Connell T.C.; Young E.D.; Scott K.; Buckingham C.M.; Iacumin P.; Brasier M.D. (My University, 2001)
Data presented herein form part of a pilot study to reconstruct palaeoenvironment using isotopic data from 200 ka collagen and skeletal remains. To date such a study has only been possible on materials of up to 120 ka, due to poor preservation, but amino acid compositional analyses of mammal molar collagen herein indicate excellent preservation of the 200 ka collagen. Samples studied were found in association with faunal evidence for a temperate climate, and oxygen and carbon isotope data support this evidence. Collagen N 15 N values, however, are akin to those typically found in collagen from modern semi-arid to arid environments. Similar data have been reported for the Eemian interglacial, and it is likely that these data reflect specific environmental adaptations, as opposed to aridity. This pilot study emphasises the need for complementary isotopic and stratigraphical analyses in palaeoenvironmental studies.